(3WjHI GdfTQ aj GdbQGAGJ GdYTQs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , J (B833 (3g` s ((3eOQSI YGTb HGTG (B_ (3GdbSWfWjfjI s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd eMeO gh GHf GdLRQi jGPG GdLdGd GQMeg hGSJQ hGZaQ GdMeO ddg Ydi eGjSQg ef fTQ efbhd MQha GdYTQI s
(3BNQgG (B:s
(3QhGjI HTQWgG GdeYJHQ hbGdg eMeO Hf GdLRQi QMeg HaVdg GdQMef aXfg ef LhOg GdZaQGf hGdMeO ddg hUd QH Ydi GdQVi eMeO hGdUMH s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfGhjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B275 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B292 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B188s
Keywords: (3GdbQGAGJ hGdJLhjOs